Outcomes of pregnancies complicated by beta-thalassemia/hemoglobin E disease - Suchaya Luewan (2018)
Objective: To assess the outcomes of pregnancies affected by beta-thalassemia/hemoglobin E (β-thal/HbE) disease. Methods: A retrospective cohort study was conducted with 54 women with singleton pregnancies complicated by β-thal/HbE disease only. The controls-to-cases ratio was 2:1. Results: Although maternal outcomes were similar in both groups, gestational age at birth and birth weight were significantly lower in the study group and the cesarean delivery rate was significantly higher in that group (relative risk [RR], 2.1). The incidences of fetal growth restriction, preterm birth, and low birth weight were also significantly higher in the study group, with RRs of 2.8, 2.7, and 5.6, respectively. Conclusion: Pregnancies affected by β-thal/HbE disease were significantly associated with an increased risk of fetal growth restriction, preterm birth, and low birth weight. © 2008 Elsevier Ireland Ltd. All rights reserved.